Umberto Eco - autobiograf? - Regina Lubas-Bartoszyńska (Przestrzenie Teorii)
This text shows that U. Eco is an autobiographer in only some sense of the word. He has not written an autobiobiographical text in which he would present a segment of his life. However, he told the history of his novelistic work and presented his intellectual train of thought in his essays, interviews, introductions to his works. There also exists an indirect autobiographism in Eco, which expresses signs of the author's life and of his personality dispersed in his interpretative and theoretical writings on literature, aesthetics, history, in his feuilletons and in his novels. Five types of autobiographism have been distinguished in Eco as well as five autobiographical strategies within the indirect autobiographism. The first strategy - a strong presence of autorial I in the text - is not sufficient and requires support of some other of the strategies discussed.